Manufacturing method for improving magnetic performance of M-type permanent magnetic ferrite

By mixing pre-sintered material A and pre-sintered material B in a specific proportion, adding an appropriate amount of additives during the sintering process, and adopting a two-stage sintering process, the complex problem of improving the magnetic performance of M-type permanent magnet ferrite in the prior art is solved, and the significant improvement of magnetic performance and simplification of production management is achieved.

CN119822802AActive Publication Date: 2025-04-15ANHUI SINOMAG TECH
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411994164.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-15
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

When improving the magnetic properties of M-type permanent magnet ferrite, the prior art requires the introduction of a variety of rare earth elements, resulting in complex raw material management and is not conducive to large-scale production.

Method used

By selecting two different prefixed materials A and prefixed materials B, mixing them in a specific proportion, and adding an appropriate amount of additives during the sintering process, the microstructure of the material is optimized.

Benefits of technology

It significantly improves the magnetic permeability, residual magnetism and maximum magnetic energy product of M-type permanent magnet ferrite, simplifies production management, reduces production complexity, and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005224241830000081
    Figure BDA0005224241830000081
Patent Text Reader

Abstract

The invention discloses a manufacturing method for improving the magnetic performance of M-type permanent magnetic ferrite, and belongs to the technical field of permanent magnetic material preparation. The preparation method comprises the following steps: selecting a pre-sintered material A and a pre-sintered material B, uniformly mixing the pre-sintered material A and the pre-sintered material B according to a mass ratio of (9: 1)-(2.5: 7.5), adding an additive, and carrying out ball milling, compression molding, sintering and other processes to prepare the M-type permanent magnetic ferrite. According to the invention, two different pre-sintering materials are mixed as a ferrite sintering raw material, the pre-sintering material A and the pre-sintering material B have obvious difference due to different raw materials and preparation processes, the two pre-sintering materials are reasonably proportioned, additives are added, and an optimized sintering process is combined, so that the residual magnetism and coercive force of the M-type permanent magnetic ferrite are improved, and the sintering performance of the M-type permanent magnetic ferrite is improved. And the mixing ratio of the two pre-sintered materials can be adjusted according to specific product performance requirements, so that large-scale production and flexible modification are facilitated, and the high-performance magnet has a wider practical value in the application field of high-performance magnets.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of permanent magnetic material preparation, and in particular relates to a manufacturing method for improving the magnetic properties of M-type permanent magnetic ferrite. Background Art

[0002] Permanent magnetic materials, also known as hard magnetic materials, refer to magnetic materials that, after being magnetized by an external magnetic field, can retain their magnetism for a long time when the external magnetic field is removed, and have high residual magnetic induction intensity and high coercive force. Permanent magnetic materials can be roughly divided into several categories, including metal permanent magnetic materials, ferrite permanent magnetic materials and rare earth permanent magnetic materials.

[0003] Permanent ferrite material is a compound with uniaxial anisotropy and hexagonal structure made by ceramic process with iron red (or iron scale) and strontium carbonate (or barium carbonate) as main raw materials. It is classified into spinel type, garnet type, magnetoplumbite type (M type), W type and perovskite type according to crystal structure. Different types of permanent ferrite materials have different magnetic properties.

[0004] M-type permanent ferrite is a hard magnetic material with a hexagonal crystal structure. It is mainly composed of barium (Ba) or strontium (Sr) replacing the A-site ions in ferrite to form AFe. 12 O 19 (A=Ba,Sr) compounds. With high coercivity and magnetic energy product, this type of material is widely used in motors, speakers, sensors and other fields. However, compared with rare earth permanent magnets, its magnetic properties are significantly lower, which limits its application in high-end fields. Therefore, the development of a new method that can effectively improve the magnetic properties of M-type permanent ferrite has important industrial value and market prospects.

[0005] The existing method for improving the magnetic properties of M-type permanent magnet ferrite is usually to introduce rare earth elements and other ions to replace part of Fe or Sr ions, that is, to improve the magnetic properties of M-type permanent magnet ferrite through ion substitution technology (such as La-Co co-substitution). The introduction method is mostly to add materials containing rare earth elements and other ions in the raw material formula for preparing pre-sintered materials, which requires strict control of the proportion of each element. From the perspective of comprehensive performance, the existing technology requires the introduction of multiple rare earth elements to simultaneously improve performance, which makes raw material management complicated and is not conducive to large-scale production. Summary of the invention

[0006] The object of the present invention is to provide a manufacturing method for improving the magnetic properties of M-type permanent ferrite, which can significantly improve the magnetic permeability, remanence and maximum magnetic energy product of ferrite, simplify production management and reduce its complexity.

[0007] The purpose of the present invention can be achieved through the following technical solutions:

[0008] The present invention provides a method for manufacturing an M-type permanent ferrite for improving magnetic properties, comprising the following steps:

[0009] Step 1: Select pre-burned material A and pre-burned material B, mix them evenly in a mass ratio of A:B=(9:1) to (2.5:7.5), and obtain a mixed pre-burned material;

[0010] Step 2, adding additives to the mixed pre-sintered material, fully mixing and wet ball milling, and drying to obtain a mixture;

[0011] Step 3: The mixture is pressed into a green body, the green body is sintered to obtain a sintered product, the sintered product is naturally cooled to room temperature and then allowed to stand for 12-24 hours, and then ground and cut to obtain an M-type permanent magnet ferrite;

[0012] The pre-sintered material A is a pre-sintered material of high-performance permanent ferrite, and the molecular formula of the high-performance permanent ferrite is Sr x Ca y La 1-x-y Fe n Co z Zn m O 19 , where 0.01≤x≤0.25, 0.05≤y≤0.35, 6.9≤n≤11.8, 0.01≤z≤0.25, 0.01≤m≤0.12;

[0013] The pre-sintered material B is a pre-sintered material of high remanence permanent ferrite, and the molecular formula of the high remanence permanent ferrite is Ca x La 1-x Fe n Zn m O 19 Pre-sintered material, wherein 0.01≤x≤0.65, 5.8≤n≤11.9, 0.01≤m≤0.2.

[0014] The two different pre-burned materials are mixed and then sintered. On the one hand, based on the needs of product applications, the two pre-burned materials can be mass-produced in actual production, and then the mixing ratio can be adjusted according to specific performance requirements to prepare permanent ferrites with different comprehensive properties, which is conducive to mass production and flexible modification.

[0015] Furthermore, the pre-sintered material A is prepared as follows:

[0016] S1, based on the molecular formula Sr x Ca y La 1-x-y Fe n Co z Zn m O 19The mass of SrCO3, CaCO3, La2O3, Fe2O3, Co3O4 and ZnO is calculated by the molar ratio, and then weighed to obtain the ingredients;

[0017] S2, mixing the ingredients to obtain a mixture, and wet-grinding the mixture for 0.5-6h to obtain a grind;

[0018] S3. Dry the ground material until the moisture content is less than 2%, crush it through an 80-mesh sieve, pre-calcine it at 1220-1280° C. for 50-250 min, and crush it to obtain pre-calcined material A.

[0019] Furthermore, the pre-sintered material B is prepared as follows:

[0020] (1) Based on the molecular formula Ca x La 1-x Fe n Zn m O 19 The masses of CaCO3, La2O3, Fe2O3 and ZnO are calculated by the molar ratio, and then weighed to obtain the ingredients;

[0021] (2) mixing the ingredients to obtain a mixture, and wet-grinding the mixture for 0.5-6 hours to obtain a grind;

[0022] (3) The ground material is dried to a moisture content of less than 2%, crushed to pass through an 80-mesh sieve, and pre-calcined at 1220-1280° C. for 50-250 min to obtain pre-calcined material B.

[0023] Furthermore, the additive is added in an amount of 0.3%-3.5% of the mass of the mixed pre-sintered material. Adding appropriate additives to the mixed pre-sintered material has an improvement effect, but its amount must be strictly controlled. Excessive addition may cause material performance to deteriorate or even produce harmful effects.

[0024] Furthermore, the additives include calcium carbonate, silicon dioxide, and sorbitol. Calcium carbonate and silicon dioxide as additives can inhibit abnormal grain growth, thereby optimizing the microstructure of the material, and calcium oxide generated by the decomposition of calcium carbonate can play a fluxing role, reduce the reaction temperature, promote the solid phase reaction, and improve the density and magnetic properties of the product. The main function of adding sorbitol is to act as a dispersant, which can effectively improve the crystal structure and particle size distribution through steric stabilization.

[0025] Furthermore, the additive also includes cobalt tetroxide. Cobalt tetroxide as an additive can significantly improve the magnetic properties of permanent ferrite.

[0026] Furthermore, in step 2, the grinding medium used in the ball milling is zirconia balls or bearing steel balls, the ball diameter is 3-8 mm, the rotation speed of the ball mill is 60-300 r / min, and the ball milling time is 5-20 h.

[0027] Furthermore, the average particle size of the mixture is 0.7-0.9 μm.

[0028] Furthermore, the strength of the external magnetic field applied during the pressing process is 800-1500 kA / m.

[0029] Further, the sintering includes a preliminary sintering stage and a final sintering stage;

[0030] The temperature of the preliminary sintering stage is 800°C-1100°C and lasts for 2-3 hours;

[0031] The temperature of the final sintering stage is 1200°C-1330°C and lasts for 4-6 hours.

[0032] The sintering process is crucial in the preparation of ferrite. By setting the sintering process into two-stage sintering, the microstructure of the ferrite material can be better controlled and the magnetic properties can be improved. In the initial sintering stage, the moisture in the green body is evenly reduced, and the contact of the particles in the body is promoted at the beginning of sintering, and a partial solid-phase reaction is carried out. In the final sintering stage, due to the high temperature, the solid-phase reaction rate is faster. The core formed by the partial solid-phase reaction in the initial sintering stage further reacts, the reaction is more complete, and the grains in the resulting sintered material are more uniform and the magnetic properties are better.

[0033] Furthermore, the sintering is performed in air or oxygen atmosphere.

[0034] Furthermore, the remanence Br of the permanent ferrite is ≥4650Gs, the maximum magnetic energy product (BH) max is ≥5.05MGOe, the correction ratio Hk / Hcj is ≥0.94, and the relative magnetic permeability is ≥1.05.

[0035] Beneficial effects of the present invention:

[0036] The present invention uses two different pre-sintered materials as ferrite sintering raw materials. The pre-sintered materials A and B have different raw materials and preparation processes, and their components have obvious differences and different performance focuses. The present invention not only improves the remanence and coercive force of the M-type permanent magnet ferrite, but also enhances the overall stability and temperature resistance of the material by reasonably proportioning the two pre-sintered materials and adding additives, combined with an optimized sintering process. This method can not only effectively improve product performance, but also is easy to operate, suitable for industrial production, and has strong market competitiveness. DETAILED DESCRIPTION

[0037] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] The preparation methods of the pre-burned material A and the pre-burned material B in the following examples and comparative examples are as follows:

[0039] Preparation of pre-sintered material A:

[0040] S1, based on the molecular formula Sr 0.2 Ca 0.1 La 0.7 Fe 10.5 Co 0.21 Zn 0.12 O 19 The mass of SrCO3, CaCO3, La2O3, Fe2O3, Co3O4 and ZnO is calculated by the molar ratio, and then weighed to obtain the ingredients;

[0041] S2, mixing the ingredients to obtain a mixture, and wet-grinding the mixture for 5 hours to obtain a grind;

[0042] S3. Dry the ground material until the moisture content is less than 2%, crush it through an 80-mesh sieve, pre-calcine it at 1260° C. for 5200 min, and crush it to obtain pre-calcined material A.

[0043] Preparation of pre-burned material B:

[0044] (1) Based on the molecular formula Ca 0.45 La 0.55 Fe 10.5 Zn 0.2 O 19 The masses of CaCO3, La2O3, Fe2O3 and ZnO are calculated by the molar ratio, and then weighed to obtain the ingredients;

[0045] (2) mixing the ingredients to obtain a mixture, and wet-grinding the mixture for 5 hours to obtain a grind;

[0046] (3) The ground material is dried to a moisture content of less than 2%, crushed to pass through an 80-mesh sieve, and pre-calcined at 1260° C. for 200 min to obtain pre-calcined material B.

[0047] Example 1

[0048] Step 1: Select pre-burned material A and pre-burned material B, mix them evenly in a mass ratio of A:B=9:1 to obtain a mixed pre-burned material;

[0049] Step 2: Add additives to the mixed pre-sintered material, the additives include calcium carbonate, silicon dioxide, sorbitol and cobalt oxide, calculated by the percentage of the mass of the mixed pre-sintered material, calcium carbonate: 0.20%, silicon dioxide: 0.33%, sorbitol 0.30%, cobalt oxide: 0.95%. The mixed pre-sintered material and the additives are fully mixed and wet-milled, the grinding medium used in the ball milling is zirconium oxide balls, the ball diameter is 5mm, the speed of the ball mill is 200r / min, the ball milling time is 10h, and the mixture is obtained after drying, and the average particle size of the mixture is 0.8μm;

[0050] Step 3: The mixture is pressed and molded under an external magnetic field strength of 1000 kA / m to obtain a green body, the size of the green body is 40 mm in diameter and 15 mm in height, and the green body is placed in a high-temperature furnace for sintering. A two-stage sintering process is adopted, firstly, preliminary sintering is performed at 1100°C for 2 hours, and the furnace is cooled to below 100°C, and then final sintering is performed at 1285°C for 4 hours. The whole process is carried out in an oxygen atmosphere to obtain a sintered product;

[0051] Step 4: The sintered product is naturally cooled to room temperature and then allowed to stand for 12 hours, and then ground and cut to obtain permanent ferrite.

[0052] Example 2

[0053] The only difference from Example 1 is that the mass ratio of pre-burned material A to pre-burned material B is adjusted to A:B=8:2, and the amount of additives added is different, as follows:

[0054] Calcium carbonate: 0.53%, silicon dioxide: 0.32%, sorbitol 0.30%, cobalt tetroxide: 0.60%.

[0055] Other conditions and steps are the same as in Example 1.

[0056] Example 3

[0057] The only difference from Example 1 is that the mass ratio of pre-burned material A to pre-burned material B is adjusted to A:B=7:3, and the amount of additives added is different, as follows:

[0058] Calcium carbonate: 0.29%, silicon dioxide: 0.37%, sorbitol 0.30%, cobalt tetroxide: 0.85%.

[0059] Other conditions and steps are the same as in Example 1.

[0060] Example 4

[0061] The only difference from Example 1 is that the mass ratio of pre-burned material A to pre-burned material B is adjusted to A:B=6:4, and the amount of additives added is different, as follows:

[0062] Calcium carbonate: 0.35%, silicon dioxide: 0.36%, sorbitol 0.30%, cobalt tetroxide: 0.80%.

[0063] Other conditions and steps are the same as in Example 1.

[0064] Example 5

[0065] The only difference from Example 1 is that the mass ratio of pre-burned material A to pre-burned material B is adjusted to A:B=5:5, and the amount of additives added is different, as follows:

[0066] Calcium carbonate: 0.41%, silicon dioxide: 0.35%, sorbitol 0.30%, cobalt tetroxide: 0.75%.

[0067] Other conditions and steps are the same as in Example 1.

[0068] Example 6

[0069] The only difference from Example 1 is that the mass ratio of pre-burned material A to pre-burned material B is adjusted to A:B=4:6, and the amount of additives added is different, as follows:

[0070] Calcium carbonate: 0.47%, silicon dioxide: 0.34%, sorbitol 0.30%, cobalt tetroxide: 0.70%.

[0071] Other conditions and steps are the same as in Example 1.

[0072] Example 7

[0073] The only difference from Example 1 is that the mass ratio of pre-burned material A to pre-burned material B is adjusted to A:B=3:7, and the amount of additives added is different, as follows:

[0074] Calcium carbonate: 0.53%, silicon dioxide: 0.33%, sorbitol 0.30%, cobalt tetroxide: 0.65%.

[0075] Other conditions and steps are the same as in Example 1.

[0076] Example 8

[0077] The only difference from Example 1 is that the mass ratio of pre-burned material A to pre-burned material B is adjusted to A:B=2.5:7.5, and the amount of additives added is different, as follows:

[0078] Calcium carbonate: 0.56%, silicon dioxide: 0.33%, sorbitol 0.30%, cobalt tetroxide: 0.63%.

[0079] Other conditions and steps are the same as in Example 1.

[0080] Comparative Example 1

[0081] Compared with Example 1, the mass ratio of pre-burned material A and pre-burned material B in this comparative example is adjusted to A:B=10:0, and the amount of additives added is different, as follows:

[0082] Calcium carbonate: 0.12%, silicon dioxide: 0.40%, sorbitol 0.30%, cobalt tetroxide: 1.00%.

[0083] Other conditions and steps are the same as in Example 1.

[0084] Comparative Example 2

[0085] Compared with Example 1, the mass ratio of pre-burned material A and pre-burned material B in this comparative example is adjusted to A:B=0:10, and the amount of additives added is different, as follows:

[0086] Calcium carbonate: 0.70%, silicon dioxide: 0.30%, sorbitol 0.30%, cobalt tetroxide: 0.50%.

[0087] Other conditions and steps are the same as in Example 1.

[0088] Comparative Example 3

[0089] Compared with Example 1, the mass ratio of pre-sintered material A to pre-sintered material B in this comparative example is adjusted to A:B=9.5:5, and the amount of additives added is different, as follows:

[0090] Calcium carbonate: 0.15%, silicon dioxide: 0.35%, sorbitol 0.35%, cobalt tetroxide: 0.20%.

[0091] Other conditions and steps are the same as in Example 1.

[0092] Comparative Example 4

[0093] Compared with Example 1, the mass ratio of pre-burned material A and pre-burned material B in this comparative example is adjusted to A:B=1:9, and the amount of additives added is different, as follows:

[0094] Calcium carbonate: 0.18%, silicon dioxide: 0.39%, sorbitol 0.30%, cobalt tetroxide: 0.90%.

[0095] Other conditions and steps are the same as in Example 1.

[0096] The performance of the permanent ferrites prepared in Examples 1 to 7 and Comparative Examples 1 to 3 was tested, and the results are shown in Table 1:

[0097] Table 1

[0098]

[0099] It can be seen from Table 1 that in Examples 1 to 8, the magnetic properties of the finished products are controlled by adjusting the ratio of pre-sintered material A to pre-sintered material B. Combined with Comparative Examples 1 to 4, it can be seen that the permanent magnet ferrite prepared according to the ratio in the embodiments has better comprehensive magnetic properties, among which the maximum magnetic energy product and the correction ratio are significantly improved, and it has a wider practical value in the application field of high-performance magnets.

[0100] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0101] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for improving the magnetic properties of M-type permanent ferrite, characterized in that: The steps include: Step 1: Select pre-burned material A and pre-burned material B, mix them evenly in a mass ratio of A:B=(9:1) to (2.5:7.5), and obtain a mixed pre-burned material; Step 2, adding additives to the mixed pre-sintered material, fully mixing and wet ball milling, and drying to obtain a mixture; Step 3: The mixture is pressed into a green body, the green body is sintered to obtain a sintered product, the sintered product is naturally cooled to room temperature and then allowed to stand for 12-24 hours, and then ground and cut to obtain an M-type permanent magnet ferrite; The pre-sintered material A is a pre-sintered material of high-performance permanent ferrite, and the molecular formula of the high-performance permanent ferrite is Sr x Ca y La 1-x-y Fe n Co z Zn m O 19 , where 0.01≤x≤0.25, 0.05≤y≤0.35, 6.9≤n≤11.8, 0.01≤z≤0.25, 0.01≤m≤0.12; The pre-sintered material B is a pre-sintered material of high remanence permanent ferrite, and the molecular formula of high remanence permanent ferrite is Ca x La 1- x Fe n Zn m O 19 Pre-sintered material, wherein 0.01≤x≤0.65, 5.8≤n≤11.9, 0.01≤m≤0.

2.

2. A method for improving the magnetic properties of M-type permanent ferrite according to claim 1, characterized in that: The preparation of the pre-sintered material A is as follows: S1, based on the molecular formula Sr x Ca y La 1-x-y Fe n Co z Zn m O 19 The mass of SrCO3, CaCO3, La2O3, Fe2O3, Co3O4 and ZnO is calculated by the molar ratio, and then weighed to obtain the ingredients; S2, mixing the ingredients to obtain a mixture, and wet-grinding the mixture for 0.5-6h to obtain a grind; S3. Dry the ground material until the moisture content is less than 2%, crush it through an 80-mesh sieve, pre-calcine it at 1220-1280° C. for 50-250 min, and crush it to obtain pre-calcined material A.

3. A method for improving the magnetic properties of M-type permanent ferrite according to claim 1, characterized in that: The preparation of the pre-sintered material B is as follows: (1) Based on the molecular formula Ca x La 1-x Fe n Zn m O 19 The masses of CaCO3, La2O3, Fe2O3 and ZnO are calculated by the molar ratio, and then weighed to obtain the ingredients; (2) mixing the ingredients to obtain a mixture, and wet-grinding the mixture for 0.5-6 hours to obtain a grind; (3) The ground material is dried to a moisture content of less than 2%, crushed to pass through an 80-mesh sieve, and pre-calcined at 1220-1280° C. for 50-250 min to obtain pre-calcined material B.

4. The method for manufacturing an M-type permanent ferrite according to claim 1, characterized in that: The additive is added in an amount of 0.3% to 3.5% of the mass of the mixed pre-sintered material.

5. The method for manufacturing an M-type permanent ferrite according to claim 1, characterized in that: The additives include calcium carbonate, silicon dioxide, sorbitol and cobalt tetroxide; The dosage of each component in the additive is calculated as follows based on the percentage of the mass of the mixed pre-sintered material: Calcium carbonate: 0.20%-0.58%, silicon dioxide: 0.32%-0.36%, sorbitol: 0.30%, cobalt tetroxide: 0.60%-0.95%.

6. The method for manufacturing an M-type permanent ferrite according to claim 1, characterized in that: The average particle size of the mixture is 0.7-0.9 μm.

7. The method for manufacturing an M-type permanent ferrite according to claim 1, characterized in that: The strength of the external magnetic field applied during the pressing process is 800-1500 kA / m.

8. The method for manufacturing an M-type permanent ferrite according to claim 1, characterized in that: The sintering includes a preliminary sintering stage and a final sintering stage; The temperature of the preliminary sintering stage is 800°C-1100°C and lasts for 2-3 hours; The temperature of the final sintering stage is 1200°C-1330°C and lasts for 4-6 hours.

9. The method for manufacturing an M-type permanent ferrite according to claim 1, characterized in that: The sintering is performed in air or oxygen atmosphere.

10. The method for manufacturing an M-type permanent ferrite for improving magnetic properties according to claim 1, characterized in that: The permanent ferrite has a remanence Br≥4650Gs, a maximum magnetic energy product (BH) max≥5.05MGOe, a correction ratio Hk / Hcj≥0.94, and a relative magnetic permeability≥1.05.

Citation Information

Patent Citations

  • Preparation method of high-performance ferrite magnetic body and magnetic body

    CN103979950A

  • Recycling and preparing method of permanent magnetic ferrite and magnet thereof

    CN104140258A

  • Permanent ferrite and preparation method thereof

    CN105418062A

  • Preparation method of high-performance permanent magnet ferrite magnet and magnet

    CN107382303A

  • Isotope coordination sintered Ca-La-Co ferrite and preparation method thereof

    CN107640967A